2009
DOI: 10.1002/app.30115
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring cure in epoxies containing carbon nanotubes with an optical‐fiber Fresnel refractometer

Abstract: Fresnel refractometry was used to follow the changes in the refractive index during the isothermal curing of a simple difunctional epoxy resin, a commercial formulated multifunctional epoxy blend, and the same two resin systems modified by the addition of multiwalled carbon nanotubes. The refractive index change, monitored via an embedded optical fiber, was correlated with the degree of cure established from isothermal differential scanning calorimetry measurements. A good correlation was established in all ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 34 publications
2
21
0
Order By: Relevance
“…8a, and is similar to that reported by Dimopoulos et al [15]. A 1550nm superluminescent diode (Covega, SLD1005) was used at 500mA with a sine-wave modulation of 9kHz and a current amplitude of ±12mA from a function generator (Stanford Research Systems, SRS DS345).…”
Section: Methodssupporting
confidence: 58%
See 1 more Smart Citation
“…8a, and is similar to that reported by Dimopoulos et al [15]. A 1550nm superluminescent diode (Covega, SLD1005) was used at 500mA with a sine-wave modulation of 9kHz and a current amplitude of ±12mA from a function generator (Stanford Research Systems, SRS DS345).…”
Section: Methodssupporting
confidence: 58%
“…The measurement principle is that changes in the refractive index of the external medium will induce a change in the Fresnel reflection at the silica / external interface [15]. That interface can be provided by a simple cleaved fibre endface or, as we show here, a ball lens.…”
Section: A Optical Fibre Refractometrymentioning
confidence: 98%
“…To provide an independent measurement of the cure, a fibre optic Fresnel measurement system that had been previously calibrated was used. The Fresnel refractometer provides a localized measurement at the tip of the fibre by measuring the intensity of the light reflected from the fibre end and comparing it with a reference channel 11 . The experimental setup that was used for monitoring cure was one used previously 2 .…”
Section: Methodsmentioning
confidence: 99%
“…More recently, Mahendran et al demonstrated a multifunctional sensor system where a conventional fiber‐coupled FTIR near‐infrared spectrometer was used to monitor four independent parameters simultaneously: strain, temperature, refractive index, and cross‐linking kinetics of an epoxy/amine resin system . Fiber‐optic Fresnel sensors have also been used for cure monitoring of thermoset resins containing fillers and during resin infusion …”
Section: Introductionmentioning
confidence: 99%